The new dialectic : conversational contexts of argument - Walton, Douglas N. (Toronto studies in philosophy., 1998)
Because developments in informal logic have been based, for the most part, on idealized and abstract models, the tools available for argument analysis are not easily adapted to the needs of everyday argumentation. In this book Douglas Walton proposes a new and practical approach to argument analysis based on his theory that different standards for argument must apply in the case of different types of dialogue. By refining and extending the existing formal classifications of dialogue, Walton shows that each dialogue type, be it inquiry, negotiation, or critical discussion, has its own set of goals. He goes on to demonstrate that an argument can best be evaluated in terms of its contribution, positive or negative, to the goals of the particular dialogue it is meant to further. In this way he illustrates how argument can be brought into the service of many types of dialogue, and thus has valuable uses that go well beyond the mere settling of disputes and differences. By reaching back to the Aristotelian roots of logic as an applied, practical discipline and by formulating a new framework of rationality for evaluating arguments, Douglas Walton restores a much-needed balance to argument analysis. This book complements and extends his Argument Structure: A Pragmatic Theory (University of Toronto Press, 1996).